Sciatic Nerve Injection Palsy in Children, Electrophysiologic Pattern and Outcome: A Case Series Study - TOOPCHIZADEH, Vahideh; BARZEGAR, Mohammad; HABIBZADEH, Afshin (Iranian Journal of Child Neurology, 2015)
How to Cite This Article: Toopchizadeh V, Barzegar M, Habibzadeh A. Sciatic Nerve Injection Palsy in Children, Electrophysiologic Pattern and Outcome: A Case Series Study. Iran J Child Neurol. Summer 2015;9(3):69-72. Abstract Sciatic nerve injury is one of the frequent mononeuropathies in children that occurs due to different causes such as nerve compression, trauma and stretch during surgery. Gluteal injection is an uncommon cause of sciatic injury in developed countries. Poor techniques and frequent injections are the common cause of injection palsy. Proneal division of the sciatic nerve is more prone to injury due to anatomic and structural characteristics. The diagnosis is based on electrophysiological studies and the recovery rate is poor. In this study, in a period of 2 years between 2012 and 2013, we report seven children under 6 years old (three females and four males) with abnormal gait and foot pain following gluteal injection in pediatric electrodiagnostic center. Five children had proneal component and two with tibial component injuries. Five children were followed for one year and only one showed good recovery.